76.0k views
5 votes
Some one help me please

Some one help me please-example-1

1 Answer

2 votes

For this case we have that by power properties it is fulfilled:


(a ^ n) ^ m = a ^ {n * m}

Now, we can rewrite the expression as:


\frac {64g ^ 9 * h ^ 6 * k ^ {12}} {8g ^ 3 * h ^ 2} -h ^ {25} k ^ {15} =

We also have by definition of properties of powers that:


\frac {a ^ m} {a ^ n} = a ^ {m-n}

So:


8g ^ {9-3} * h ^ {6-2} * k ^ {12} -h ^ {25} k ^ {15} =\\8g ^ 6 * h ^ 4 * k^(12) -h^(25) * k^(15)

Answer:

Option D

User Solgar
by
5.6k points